2003
DOI: 10.1159/000075738
|View full text |Cite
|
Sign up to set email alerts
|

A refined comparative map between porcine chromosome 13 and human chromosome 3

Abstract: We report here the localisation of BAIAP1 (13q24), HTR1F (13q45), PTPRG (13q23) and UBE1C (13q24) by fluorescence in situ hybridisation (FISH), and BAIAP1 (Swr2114; 21 cR; LOD = 11.03), GATA2 (Sw2448; 37 cR; LOD = 8.26), IL5RA (Swr2114; 64 cR; LOD = 3.85), LMCD1 (Sw2450; 61 cR; LOD = 4.73), MME (CP; 50 cR; LOD = 7.75), RYK (Swc22; 12 cR; LOD = 18.62) and SGU003 (Sw1876; 6 cR; LOD = 16.99) by radiation hybrid (RH) mapping to porcine chromosome 13 (SSC13). The mapping of these 10 different loci (all mapped to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…However, we were not able to establish the precise localization of the GATA2 gene due to the limited resolution of the FISH technique. Based on our results and results obtained by radiation hybrid mapping (Van Poucke et al, 2003), we can predict that the GATA2 gene is located in the proximal part of SSC13q31.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…However, we were not able to establish the precise localization of the GATA2 gene due to the limited resolution of the FISH technique. Based on our results and results obtained by radiation hybrid mapping (Van Poucke et al, 2003), we can predict that the GATA2 gene is located in the proximal part of SSC13q31.…”
Section: Resultssupporting
confidence: 60%
“…Based on comparative chromosome painting studies it has been shown that a large part of porcine chromosome 13 (13q11 ] q46) is homologous to human chromosome 3 and a small distal part of SSC13 is homologous to HSA21 (Goureau et al, 1996). However, comparative mapping revealed several interchromosomal differences between SSC13 and HSA3 (Van Poucke et al, 2003). Four chromosome blocks were identified in HSA3 that correspond to SSC13.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene PTPRG is a member belonging to the classic tyrosine phosphatase gene family, which includes receptor genes and non-receptor genes. PTPRG is a member of receptor gene, and is situated at 3p14 chromosome [20][21][22] . Previous researches observed methylation extinguishments of other genes that belong to the same family of PTPRG, such as PTPRN2, PTPRO, etc, in hepatic cancer [23] .…”
Section: Figurementioning
confidence: 99%